Online Learning Service Application Design Using Flutter and Laravel Framework - Yusuf Kurnia; Geraldi Aditya (Komunitas Dosen Indonesia, 2022)
Bimbel Prisma is an elementary-high school level tutoring institution located at Jalan Pelopor Blok O8 RT.007 RW.011, Tegal Alur District, Kalideres Village, West Jakarta. Prisma Bimbel was founded because of the large number of requests from the community who wanted their children who occupy elementary to high school seats to improve their performance in school. The use of the Flutter framework as a Front-End Mobile Application and this application has a Video Conference using Flutter making application design easier with a collection of widgets that have been provided and can be customized as needed and have high performance which will make the application more comfortable to use. By using the Laravel framework, it makes backend design in the form of an Application Programming Interface (API) easier and saves time by using the Restful Controller feature and has strong security in protecting the backend so that user data privacy becomes more secure. With the online learning service application, it is able to improve the learning process for students by studying material or answering questions that can be accessed via the internet so that it helps improve the quality of education and is able to improve the performance process for staff and teachers without having to come to the office because it is online based but can be productive. in handling administrative services or learning activities.